2019
DOI: 10.1177/1708538118813228
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured popliteal artery aneurysms

Abstract: Background Rupture is a recognised complication of ruptured popliteal artery aneurysms that requires emergency intervention. There is little evidence collating the presentation, intervention and outcomes of ruptured popliteal artery aneurysms. Objective The primary aim of this study was to deduce the sequelae following different management modalities of ruptured popliteal artery aneurysm. Methods We performed a systematic review of all available cases reports of ruptured popliteal artery aneurysms in accordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…A literature review conducted at the time of submission of this case report showed 62 [2][3][4][5][6][7][8][9][10][11][12][13] reported cases of ruptured PAA. Most cases reported were males, with an age range of 55-96 and a mean age of 81.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review conducted at the time of submission of this case report showed 62 [2][3][4][5][6][7][8][9][10][11][12][13] reported cases of ruptured PAA. Most cases reported were males, with an age range of 55-96 and a mean age of 81.…”
Section: Discussionmentioning
confidence: 99%
“…PAA rupture is a rare but recognized presentation that requires a rapid diagnosis and treatment for limb salvage [1]. The standard treatment for such ruptures is a surgical exclusion bypass; however, a number of other management options are described in the literature [2][3][4][5][6][7][8][9][10][11][12][13]. Such options include endovascular treatment with coil embolization [10] and/or stent graft.…”
Section: Introductionmentioning
confidence: 99%
“…In largest reported series, around 2-5% of PAA that have been surgically managed were found to be ruptured within the surgery. 3,4 Management has traditionally been surgically, however, in recent years considerable development of endovascular techniques and materials has added an interesting and less invasive treatment approach, particularly in high risk patients. 3,4 At a technical level, endovascular treatment consists in exclusion of the aneurism with a stent graft.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Management has traditionally been surgically, however, in recent years considerable development of endovascular techniques and materials has added an interesting and less invasive treatment approach, particularly in high risk patients. 3,4 At a technical level, endovascular treatment consists in exclusion of the aneurism with a stent graft. Technical challenges in these situations are seen when a PAA is too large, resulting in bending and kinking of adjacent artery segments, or in an acute setting such as rupturing.…”
Section: Introductionmentioning
confidence: 99%
“…Documented microbes in their series were Salmonella spp. (3), Staphylococcus aureus (2), Escherichia coli, Campylobacter fetus, Mycobacterium bovis, Listeria, and group B Streptococcus[9].Overall, mycotic aneurysms infected with Staphylococcus epidermidis should demonstrate a generally indolent course. They may present with minimal to no clinical features of infection and are difficult to culture and diagnose.…”
mentioning
confidence: 99%